Penilaian Status Gizi Mandiri pada Balita di Kelurahan Mokoau Kota Kendari - Ellyani Abadi; Siti Hadrayanti Ananda; Habib Ihsan Mowuta (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
The nutritional status of children under five is one of the health indicators that play a role in determining the quality of the nation's generation. One of the efforts to improve nutritional status is to disseminate information related to nutrition and how to determine nutritional status independently that can be done by mothers who have toddlers. The purpose of this service is to share information related to the definition of nutritional status, how to measure the nutritional status of children under five, an instrument for measuring nutritional status and how to independently assess nutritional status for toddlers in Mokoau Village, Kendari City. The dedication method is carried out by lectures, question and answer discussions and simulations. This community service was carried out on August 7, 2020, to be precise at the Mokoau sub-district office. The target of this activity is mothers who have toddlers in Mokoau Village as many as 25 people. The results of this study can be seen that of the 25 respondents, most of them 56.0% know about the definition of nutritional status, the remaining 44.0% do not know about nutritional status, then 68% of respondents do not know how to determine nutritional status using the z-score and 32 % know how to determine nutritional status. Then most of the 60.0% knew about the tool to measure weight and 40.0% answered incorrectly when interviewed on the name of the tool to measure weight. Then 80.0% knew the name of the tool to measure height was mikrotoice and medline or meter and 20.0% answered incorrectly regarding the name of the tool to measure height. Then 80.0% of respondents knew the impact of malnutrition and only 20.0% answered incorrectly about the impact of malnutrition on children under five. This conclusion is to provide new information for mothers who have toddlers about nutrition, especially related to how to determine nutritional status independently. This Community Service Provider also motivates mothers of toddlers to actively participate in integrated service post activities, namely bringing their children regularly to integrated service posts so that they can determine the nutritional status of their children